الصلابة النفسية و علاقتها بالاحتراق النفسي لدى عينة من موظفي مؤسسة سونطراك الأغواط - لخذاري عيسى; دوة عبد الرحيم; كزواي عطالله (My University, 2023)
This study aims to know the nature of the relationship between psychological burnout and psychological hardness among the workers of the Sonatrach Corporation, through a field study that included a sample of 25 workers in the Corporation in the state of Laghouat. The Maslash scale of psychological burnout and Mukhaimer's scale of psychological hardness were used. The results of the study found the following: There is an inverse significant relationship between psychological burnout, as well as its three dimensions, and psychological hardness among Sonatrach workers. Keywords: psychological burnout, psychological hardness